Lock-in Thermography for the Development of New Materials. (2017) - Nolte, Peter W.; Malvisalo, Timo; Rimbach, A. Charlotte; Steudel, Franziska; Ahrens, Bernd; Schweizer, Stefan
Abstract: Thermal management is one of the crucial concerns for mid- and high-power white light-emitting diodes (LEDs). Most of the currently available white LEDs on the market consist of a blue LED chip coated with a yellow phosphor-polymer composite. Besides the heat-induced degradation of the phosphor-polymer composite, the so-called thermal quenching, i.e. the decrease in light output upon increasing temperature, is also a pressing issue. Both result in an efficiency decrease and in a color change of the LED. In this work, a method to determine the thermal diffusivity and the thermal conductivity of phosphors is presented using lanthanide-doped glasses as test samples. In the quest for temperature-stable phosphors with a high thermal conductivity, such luminescent glasses might represent an attractive alternative. Thermal waves are introduced to the samples by periodical heating with a laser. Lock-in infrared thermography, a non-destructive method, is used to monitor even small changes in surface temperature. The phase delay of the thermal wave passing through the sample is analyzed at different lock-in frequencies and a mathematical fitting of the phase data then provides the coefficients required to determine the thermal diffusivity. Subsequently, the thermal conductivity is calculated from the thermal diffusivity, the mass density, and the specific heat capacity.